IMPLEMENTASI PANCASILA DALAM MENGATASI KORUPSI DI INDONESIA DALAM PERSPEKTIF MAHASISWA JURUSAN TEKNIK SIPIL POLITEKNIK NEGERI SEMARANG - Wahyumi, Puji; Mahmudi, Wildana Latif; Sulaiman, Sriwahyuningsih; Mawardi, Mawardi; Devilito, Rio (Politeknik Negeri Semarang, 2024)
Pancasila education as one of the General Compulsory Courses is given in universities as an effort to re-cultivate Pancasila values in students. One effort to anticipate corruption is to foster behavior and attitudes that are in accordance with Pancasila values. For this reason, it is necessary to have a good and correct understanding among students regarding the values of Pancasila so that they can implement these values in their contribution to being involved in solving the nation's problems. The purpose of this research is to determine the understanding of Civil Engineering students at the Semarang State Polytechnic regarding the values of Pancasila, the perceptions of civil engineering students regarding the implementation of Pancasila in overcoming corruption in Indonesia. The research methodology used is descriptive analytical and qualitative. Data collection was carried out by administering questionnaires and interviews. Next, it is analyzed and expressed in quantitative form. From the research result, it was found that 97.8% of students memorized Pancasila, 96.9% understood Pancasila, 92.5% stated that corruption was contrary to the first principle, 97.4% of corruption was contrary to the second principle, 94.3% stated that corruption was contrary to the first principle. third, 99.1% of corruption is contrary to the fourth principle and 100% of students stated that corruption is contrary to the fifth principle of Pancasila.